PENGEMBANGAN MODUL PEMBELAJARAN KIMIA PADA MATERI POKOK LARUTAN ELEKTROLIT DAN NONELEKTROLIT BERBASIS INKUIRI TERBIMBING (GUIDED INQUIRY) - Eka Rahmatul Aidha (Sekolah Tinggi Teknologi Industri Padang, 2016)
Issue formal education become a common topic today is the low student learning outcomes. Based on the research conducted so far, it turns out low yields due to student learning in general chemistry students have difficulty in analyzing chemical material that is both abstract and resolve problems related to chemical reactions, this happens due to lack of understanding by students. One of the learning strategies that encourage students to seek and find something in learning is through guided inquiry strategies. In support of this strategy, the group used the system to learn and make teaching materials in the form of chemistry learning modules based on guided inquiry learning cycle. The subjects were students of class X SMA Negeri 1 Lubuk Alung. This type of research is the development of research with the development of type 4D models. Validation results showed that the chemistry learning modules in the subject matter of electrolyte and nonelectrolyte solution has a moment kappa of 0.84. These results reveal that, the product is in conformity with the curriculum and the correct concept. Field trial results show the practicality of the value of products made based on the assessment of teachers' questionnaire responses with kappa of 0.91 and a moment of assessment student questionnaire responses by 0.95. Based on the results of this study concluded that the developed learning modules are very practical for use in the learning process. It is also proved by testing students' understanding of the effectiveness of a product with an average score of 85.8. It can be concluded that using the students' understanding of chemistry learning modules in the category so well that the product is very effective for use in learning. Keywords: Learning Module Chemistry, Main Material Electrolytes and Nonelectrolytes, Guided Inquiry.